Autorregulación con la posibilidad de corrupción - Nuñez, Javier; Díaz, Guillermo; Vargas, Miguel (Estudios de Economía, 2016)
This work researches about Self Regulatory Organizations’ incentives to exertregulation of quality. The analysis is based upon an agency approach, whichinvolves the existence of a principal, who has the responsibility of monitoringthe standard of quality of goods that are provided by the SRO’s members (agents),and to report to whom doesn’t meet that. The motivation for the enforcement isreputational, given that consumers cannot observe the goods’ quality, but relyon the observation of reporting of fraud signals by the SRO to infer it. Therefore,quality emerges endogenously by the strategic interaction between the principal’sincentives to watch and the agent’s tendency towards fraud. This work analyzeshow the possibility of corruption impacts upon the SRO’s incentives for the enforcementof standards. Corruption arises when agents discovered in fraudulent activities, pay a bribe and avoid to be punished. The main result is that the morelikely equilibrium implies a level of fraud greater than in a world without possibilityof corruption. Besides, there is fraud cover up and impunity.